EFFECTIVENESS OF VARIOUS INTUBATION AIDS—BLOCKBUSTER LMA, VIDEO LARYNGOSCOPE, AND GUM ELASTIC BOUGIE IN ANTICIPATED DIFFICULT INTUBATION (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Management of anticipated difficult airway remains a critical challenge in anesthesiology. Various intubation aids such as the gum elastic bougie (GEB), Blockbuster laryngeal mask airway (LMA), and video laryngoscope (VL) have been developed to improve intubation success and patient safety. Objectives: To compare the effectiveness of gum elastic bougie, Blockbuster LMA, and video laryngoscope in patients with anticipated difficult intubation. Methods: This prospective observational study included 145 patients with predictors of difficult airway. Patients were allocated into three groups: Group G (GEB, n=75), Group L (Blockbuster LMA, n=45), and Group V (VL, n=25). Baseline demographic parameters and airway assessment variables were recorded. The primary outcome was intubation success rate, while secondary outcomes included causes of failure. Results: Baseline characteristics including age, gender, BMI, Mallampati score, thyromental distance, inter-incisor distance, neck movement, and neck circumference were comparable across groups. The overall success rate was 88.27% (128/145). Group G demonstrated the highest success rate (100%), followed by Group L (91%), while Group V showed a significantly lower success rate (48%). Failures were attributed to malposition (n=8), failed passage to pharynx (n=5), and failed ventilation (n=4). Conclusion: Gum elastic bougie proved to be the most effective and reliable intubation aid in anticipated difficult airway, demonstrating superior success rates compared to Blockbuster LMA and video laryngoscope. Its simplicity, adaptability, and high first-pass success make it a valuable tool in airway management.